FEATURES OF IMMUNOLOGICAL CHANGES IN METABOLIC SYNDROME - Khamdamov, B.Z.; Sattarov, O.T.; Isomutdinov, A.Z. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
For several decades, it has been believed that an increased inflammatory background has a great impact on glucose metabolism. For example, the expansion and infiltration of pro-inflammatory immune cells is present in several metabolic active tissues during the development of type 2 diabetes. This pro-inflammatory environment has huge implications for organ function, as seen in the development of insulin resistance, beta-cell dysfunction, and nonalcoholic steatohepatitis. The trigger or origin of this inflammatory response is still elusive. There is great opportunity to identify and describe the underlying metabolic and inflammatory pathways, however, the resulting research is often contradictory. In particular, models in experimental mice often produce inconclusive results, and numerous inflammatory messengers have a dual role. In addition, the active components of the immune system perform important physiological functions (other than pure inflammation) and have tissue responses. These results highlight that the immune system is a complex organization that is often neither pro- nor anti-inflammatory per se. In addition, a controlled (acute) inflammatory response is important for the host to control invading pathogens and remove damaged tissues.